2017
DOI: 10.1007/s10653-017-9947-0
|View full text |Cite|
|
Sign up to set email alerts
|

Date palm waste-derived biochar composites with silica and zeolite: synthesis, characterization and implication for carbon stability and recalcitrant potential

Abstract: Engineered organo-mineral composites were synthesized from date palm waste biochar and silica or zeolite via mechanochemical treatments. Date palm tree rachis (leaves) waste biomass was pre-treated with silica or zeolite minerals via ball milling and sonication prior to pyrolysis at 600 °C. The resultant organo-mineral composites and pristine materials were characterized using X-ray diffraction, thermogravimetric-differential thermal (TG-DTA), Fourier transform infrared, scanning electron microscope analyses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 52 publications
4
46
0
1
Order By: Relevance
“…A band appearing at 3426 cm −1 in the composite of nZVI-DBC was attributed to -OH stretching vibrations, which indicated the presence of a layer of FeOOH onto the surfaces of nZVI particles. A peak appearing at 2900 cm −1 in DF was designated to aliphatic C-H and O-H stretching owing to cellulose and hemicellulose, which was vanished in DBC 31 . A band around 1750 cm −1 in DF represented the existence of C=O stretching.…”
Section: Sem Xrd Ftirmentioning
confidence: 99%
See 1 more Smart Citation
“…A band appearing at 3426 cm −1 in the composite of nZVI-DBC was attributed to -OH stretching vibrations, which indicated the presence of a layer of FeOOH onto the surfaces of nZVI particles. A peak appearing at 2900 cm −1 in DF was designated to aliphatic C-H and O-H stretching owing to cellulose and hemicellulose, which was vanished in DBC 31 . A band around 1750 cm −1 in DF represented the existence of C=O stretching.…”
Section: Sem Xrd Ftirmentioning
confidence: 99%
“…The maximum weight loss was in the following order: DF (81.14%) > nCD-DBC (41.01%) > DBC (62.63%) > nZVI-DBC (41.23%). Thermal stability of the materials was further estimated by calculating the recalcitrance potential (R 50 ) of ash and moisture-free TGA thermograms as reported by Ahmad et al 31 . It has been reported that materials with R 50 < 0.50 are highly degradable, 0.70 > R 50 ≥ 0.50 are marginally stable, and those with R 50 > 0.70 are highly stable 31 .…”
Section: Sem Xrd Ftirmentioning
confidence: 99%
“…Zhao et al [ 46 ] from an adsorption study suggested that the addition of silicon not only enhanced the adsorption capacity of biochar, but also effectively resisted the decrease in the adsorption capacities on BCs after aging (H 2 O 2 and H 2 SO 4 oxidation). Previous studies have also shown that silica particles might affect C arrangement and structural composition by producing a Si-C coupling system in the biochar matrix [ 47 ]. As discussed above, BC modified with silicon shows potential for enhanced metal adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…While among the biochar from UOW blends, 650M s has the highest recalcitrance despite lower graphitization compared to 650P as seen in its FTIR spectrum. 650M s has more silica inherited from M s (sec 3.1), which increases the recalcitrance through Si encapsulation of carbon [113]. In addition, the higher Fe content in 650M s (sec 3.2.2) also promotes graphitization [114] and higher recalcitrance [115].…”
Section: Thermal Oxidative Recalcitrancementioning
confidence: 99%